Development of an Automated Infrared Therapy System Based on MLX90614 Sensor for Muscle Pain Treatment - Annisa, Zhudiah; Falah, Agus Hayatal; Wisaksono, Arief; Saputra, Dwi Hadidjaja Rasjid (Newinera Publisher, 2026)
This study aims to design and evaluate an automatic infrared therapy system capable of maintaining temperature stability within a safe and controlled range. The system utilizes a non-contact infrared temperature sensor MLX90614, an ultrasonic distance sensor HC-SR04, an Arduino Uno microcontroller, and an infrared lamp regulated by a pulse width modulation (PWM) signal. Temperature control is implemented using a proportional control (P-Control) method, while sensor data is processed using a moving average filter to reduce measurement noise. Experimental testing was conducted by comparing system responses without control and with P-Control at three distance variations, namely 15 cm, 30 cm, and 45 cm. The results show that the uncontrolled system produced a temperature deviation of ±1.8°C, while the implementation of P-Control reduced the deviation to ±0.6°C at a setpoint of 45°C. However, the achieved average temperature varied depending on distance, with values ranging from 35.27°C to 42.61°C across all test conditions. These results indicate that the application of P-Control combined with a moving average filter is effective in improving temperature stability, although the heating performance is influenced by the distance between the sensor and the object. This system demonstrates potential for safer and more controlled infrared therapy applications.